If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = 3n + 1 Reorder the terms: 4 = 1 + 3n Solving 4 = 1 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 4 + -3n = 1 + 3n + -3n Combine like terms: 3n + -3n = 0 4 + -3n = 1 + 0 4 + -3n = 1 Add '-4' to each side of the equation. 4 + -4 + -3n = 1 + -4 Combine like terms: 4 + -4 = 0 0 + -3n = 1 + -4 -3n = 1 + -4 Combine like terms: 1 + -4 = -3 -3n = -3 Divide each side by '-3'. n = 1 Simplifying n = 1
| h(0)=-16t^2(1)+0(0)+12 | | h(1)=-16t^2(1)+15(1)+5 | | 6p-4(3-9)=-5p+1 | | (19b-6)-6(3b+3)=-7 | | msquared+9m=0 | | x-5/3=7 | | 4(2a-1)=-10a(a-5) | | 2x^3-10x^2=8x | | h(0)=-16t^2(1)+15(1)+12 | | 4*(x-9)=20 | | 51/5+x=8 | | -4(-2t+1)=-(-4+10t) | | 4*x-9=20 | | h(0)=-16t^2(1)+95(1)+0 | | 9x/x+3-2x-21/x+3 | | -6=y/7 | | x^30=x | | h(0)=-16t^2(1)+28(1)+5 | | -3(x+5)=4(x-1) | | -2p-4(2p+9)=6p-10 | | y^2-16y+63=0 | | h(0)=-16t^2(t)+28(t)+5 | | -4x-6y=-28 | | h(0)=-16t^2(0)+28(0)+5 | | 4+2*x=7+x | | -x+7=-16 | | 2/5p=32.7 | | 25-3(6-x)=7 | | 5x+3=-(x-21) | | 8-x*2=20+x | | 4x-2=7x-4x | | 8-x^2=20+x |